Reducing Addiction in Bipolar Disorder via Hacking the Dopaminergic System - Grunze, Heinz; Csehi, Réka; Born, Christoph; Barabássy, Ágota (Frontiers in Psychiatry, 2021)
The dopaminergic system plays a central and decisive role in substance use disorder (SUD), bipolar disorder (BD), and possibly in a subgroup of patients with refractory depression. Common genetic markers and underlying cellular processes, such as kindling, support the close link between these disorders, which is also expressed by the high rate of comorbidity. Although partial dopamine agonists/antagonists acting on D2 and D3 receptors have an established role in treating BD, their usefulness in SUD is less clear. However, dopamine D3 receptors were shown to play a central role in SUD and BD, making D2/D3 partial agonists/antagonists a potential target for both disorders. This narrative review examines whether these substances bear the promise of a future therapeutic approach especially in patients with comorbid BD and SUD.